Ceres' spectral link to carbonaceous chondrites—Analysis of the dark background materials. (11th April 2018) - Schäfer, Michael; Schäfer, Tanja; Izawa, Matthew R. M.; Cloutis, Edward A.; Schröder, Stefan E.; Roatsch, Thomas; Preusker, Frank; Stephan, Katrin; Matz, Klaus‐Dieter; Raymond, Carol A.; Russell, Christopher T.
Abstract: Ceres' surface has commonly been linked with carbonaceous chondrites (CCs) by ground‐based telescopic observations, because of its low albedo, flat to red‐sloped spectra in the visible and near‐infrared (VIS/NIR) wavelength region, and the absence of distinct absorption bands, though no currently known meteorites provide complete spectral matches to Ceres. Spatially resolved data of the Dawn Framing Camera (FC) reveal a generally dark surface covered with bright spots exhibiting reflectance values several times higher than Ceres' background. In this work, we investigated FC data from High Altitude Mapping Orbit (HAMO) and Ceres eXtended Juling (CXJ) orbit ( 140 m/pixel) for global spectral variations. We found that the cerean surface mainly differs by spectral slope over the whole FC wavelength region (0.4–1.0 μm). Areas exhibiting slopes <−10% μm −1 constitute only 3% of the cerean surface and mainly occur in the bright material in and around young craters, whereas slopes ≥−10% μm −1 occur on more than 90% of the cerean surface; the latter being denoted as Ceres' background material in this work. FC and Visible and Infrared Spectrometer (VIR) spectra of this background material were compared to the suite of CCs spectrally investigated so far regarding their VIS/NIR region and 2.7 μm absorption, as well as their reflectance at 0.653 μm. This resulted in a good match to heated CI Ivuna (heated to 200–300 °C) and a better match for CM1 meteorites, especially Moapa Valley. This possibly indicates that the alteration of CM2 to CM1 took place on Ceres.